2019 41st Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2019
DOI: 10.1109/embc.2019.8856437
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Dependence of Differential Pathlength Factor on Blood Volume and Oxygen Saturation using Monte Carlo method

Abstract: Differential Pathlength Factor (DPF) is a vital parameter for the Beer-Lambert law based calculations in estimating tissue perfusion using non-invasive optical techniques. A significant error in the measured concentration of oxyhemoglobin and deoxyhemoglobin has been reported due to the usage of wrong DPF values. The dependence of DPF on blood oxygen saturation and blood volume has never been studied earlier. In this work, a Monte Carlo model of perfused skin tissue was developed and executed at 660 nm and 940… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Thus, the actual optical pathlength is much larger than source-to-detector separation (optode spacing), and so the differential pathlength factor (DPF) was incorporated into the above equation to relate the actual optical pathlength to the source-to-detector separation [27,28]. Many studies have estimated the optical pathlength and the DPF computationally or experimentally [27][28][29][30]. Studies have shown that the DPF can be estimated directly from direct time-of-flight measurements [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the actual optical pathlength is much larger than source-to-detector separation (optode spacing), and so the differential pathlength factor (DPF) was incorporated into the above equation to relate the actual optical pathlength to the source-to-detector separation [27,28]. Many studies have estimated the optical pathlength and the DPF computationally or experimentally [27][28][29][30]. Studies have shown that the DPF can be estimated directly from direct time-of-flight measurements [27].…”
Section: Introductionmentioning
confidence: 99%
“…Phase-resolved optical spectroscopy has also been utilized to estimate the DPF [29,31]. Computationally, the Monte Carlo method was utilized to estimate the DPF in reflectance photoplethysmography [28] and blood volume and oxygen saturation [30] for two wavelengths. Moreover, researchers have investigated the DPF's dependence on optode spacing, operating wavelength, and age [32,33].…”
Section: Introductionmentioning
confidence: 99%